Boarding house selection using SAW method - Mukhlis H.; Ayshwarya B.; Nguyen P.T.; Hashim W.; Hardono; Maesaroh S.; Sagita Y.D.; Surmiasih; Sanjaya R.; Oktafianto; Shankar K.; Denisova O.P.; et al. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Determination of residence in a new area known is influenced by many factors namely location, facilities, contract systems and prices. This journal determines the criteria used in selecting a residence. These criteria were analyzed using simple additive weighting (SAW) method. The results of the analysis obtained in the form of location criteria to determine the most suitable boarding house because the existence of boarding houses in the vicinity of public facilities is highly expected for migrants in a new area. With the advancement of information technology it can answer the need to find a boarding house, and will be very helpful both from the owner and tenant side. And not only that, with this internet technology, prospective tenants can also select a boarding house that suits their wishes. Planning a system that can assist in the determination of temporary housing is needed by tenants in finding housing that fits the desired criteria. With the creation of a DSS (Decision Support System), the selection of boarding houses is expected to help resolve the problem of alternative housing. Therefore a decision support system application program is needed to determine a temporary residence or boarding house. Decision support system is a computer-based system that aims to assist decision making by utilizing data and models to solve unstructured problems. BEIESP.